1992
DOI: 10.2307/2393475
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Boundary: External Activity and Performance in Organizational Teams

Abstract: and tfie anonymous reviewers at Administrative Science Quarteriy for their support and comments. This article focuses on the activities teams use to manage their organizational environment beyond their teams. We used semistructured interviews with 38 new-product team managers in high-technotogy companies, log data from two of these teams, and questionnaires completed by members of a different set of AB new-product teams to generate and test hypotheses about teams' external activities. Results indicate that tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
1,427
7
16

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,710 publications
(1,518 citation statements)
references
References 38 publications
33
1,427
7
16
Order By: Relevance
“…There has been a significant amount of research interest in the topics of cross-functional teams (e.g., Ancona, 1990;Ancona and Caldwell, 1992;Denison et al, 1996;Dougherty, 1992) and marketing's cross-functional interfaces (e.g., Griffin and Hauser, 1996;Karmarkar, 1996;Montgomery and Webster, 1997;Workman, 1993). Given our research interest in the question of whether decisions on marketing activities should be made cross-functionally, we see three areas of related research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There has been a significant amount of research interest in the topics of cross-functional teams (e.g., Ancona, 1990;Ancona and Caldwell, 1992;Denison et al, 1996;Dougherty, 1992) and marketing's cross-functional interfaces (e.g., Griffin and Hauser, 1996;Karmarkar, 1996;Montgomery and Webster, 1997;Workman, 1993). Given our research interest in the question of whether decisions on marketing activities should be made cross-functionally, we see three areas of related research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…External activities provide access to external parties, who tend to possess non-redundant knowledge and offer different perspectives (Ancona & Caldwell, 1992;Hansen, 1999). Prior work shows that exposure to novel and contrasting viewpoints has the advantages of broadening the recipients' knowledge base, compelling consideration of alternative approaches, and prompting novel combination of ideas, resulting in the development of innovative practices that can ultimately result in better outcomes (Powell, 1998;Sutton & Hargadon, 1996).…”
Section: Inter-olas and Performancementioning
confidence: 99%
“…Prior work shows that exposure to novel and contrasting viewpoints has the advantages of broadening the recipients' knowledge base, compelling consideration of alternative approaches, and prompting novel combination of ideas, resulting in the development of innovative practices that can ultimately result in better outcomes (Powell, 1998;Sutton & Hargadon, 1996). Several studies outside health care have found a positive relationship between use of external activities and performance (Ancona & Caldwell, 1992;Choi, 2002;Wong, 2004). Given the effect that external activities can have, we propose that collaborative participants that leverage the inter-OLAs offered by collaboratives are likely to experience greater performance improvement.…”
Section: Inter-olas and Performancementioning
confidence: 99%
“…Research from an external perspective has examined both the behavioral relations between teams and their environments, such as boundary-spanning activities, scouting behaviors, and influence attempts (e.g. Tushman, 1977;Ancona & Caldwell, 1992;Gresov & Stephens, 1993), and the structural relations between teams and their environments, such as task design and reward systems (e.g. Hackman, 1987;Wageman, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…To establish that cosmopolitans and locals can be viewed as status categories, I identify their status characteristics and explain the expectations that are associated with those characteristics, focusing on work settings in which team members regularly engage in extensive boundary-spanning in order to gather knowledge to accomplish their tasks (cf. Tushman, 1977;Ancona & Caldwell, 1992). Specifically, I propose that both cosmopolitans and locals may be viewed as high in status because each is expected to enable their team to interpret knowledge obtained from outside sources accurately and appropriately for the task, although their interpretations are likely to be very different.…”
Section: Introductionmentioning
confidence: 99%